Silencing of CDKN1C (p57KIP2) is associated with hypomethylation at KvDMR1 in Beckwith–Wiedemann syndrome. Issue 11 (19th November 2003) - Diaz-Meyer, N; Day, C D; Khatod, K; Maher, E R; Cooper, W; Reik, W; Junien, C; Graham, G; Algar, E; Der Kaloustian, V M; Higgins, M J
Abstract : Context: Beckwith–Wiedemann syndrome (BWS) arises by several genetic and epigenetic mechanisms affecting the balance of imprinted gene expression in chromosome 11p15.5. The most frequent alteration associated with BWS is the absence of methylation at the maternal allele of KvDMR1, an intronic CpG island within the KCNQ1 gene. Targeted deletion of KvDMR1 suggests that this locus is an imprinting control region (ICR) that regulates multiple genes in 11p15.5. Cell culture based enhancer blocking assays indicate that KvDMR1 may function as a methylation modulated chromatin insulator and/or silencer. Objective: To determine the potential consequence of loss of methylation (LOM) at KvDMR1 in the development of BWS. Methods: The steady state levels of CDKN1C gene expression in fibroblast cells from normal individuals, and from persons with BWS who have LOM at KvDMR1, was determined by both real time quantitative polymerase chain reaction (qPCR) and ribonuclease protection assay (RPA). Methylation of the CDKN1C promoter region was assessed by Southern hybridisation using a methylation sensitive restriction endonuclease. Results: Both qPCR and RPA clearly demonstrated a marked decrease (86–93%) in the expression level of the CDKN1C gene in cells derived from patients with BWS, who had LOM at KvDMR1. Southern analysis indicated that downregulation of CDKN1C in these patients was not associated with hypermethylation at the presumptive CDKN1C promoter. Conclusions: An epimutation at KvDMR1, the absence of maternal methylation, causes the aberrant silencing of CDKN1C, some 180 kb away on the maternal chromosome. Similar to mutations at this locus, this silencing may give rise to BWS.